Learning progression of energy in secondary school physics - Azlinah Ispal (2016)
This study reported results on short-term learning progression of energy in secondary school physics. Energy concept is one of the most important ideas in all of science and useful for predicting and explaining phenomena in every scientific discipline. There are differences In how the energy concept is used across different disciplines. This matter triggers the alternative conceptions of energy not only among children, but students at university and society. This study employs a method called developmental maieutics in order to achieve the research objectives and to answer the research questions. All participants involved in two semi-structured interview sessions before and after the instructional intervention of energy concepts. There are five different situations of daily activities used as interview tools (interview-about-instance). Each interview transcribed and analysed. The cognitive level and energy concept development were analysed from both of the interviews. The development of cognitive was analysed based on Dawson-Tunik's cognitive development, while the energy concept is based on the sequence which starts from the forms and sources of energy, transformation of energy, energy transfer, and conservation of energy. The results triangulated with the reflection. Overall, all participants' conceptual knowledge increased to the higher levels, but not all of them achieved the abstract mappings level. The cognitive and conceptual knowledge of each participant · developed at different rates in a different level and in this study, conservation of energy is the most difficult concept. The researcher discusses the implication of result in a few aspects. Finally, further steps in working towards a learning progression of energy are identified.